Prevalence and Associated Risk Factors of Bovine Viral Diarrhoea (BVD) in Ruminants in Selangor - Rahman, Nur Husna Abdul; Fitri, Wan-Nor; Abu, Noor Asyikin; Suntharam, Vijayakumar; Ahmat, Nur Sakinah; Aisyah, Nur; Mahsuri, Mohd Fahmi; Abidin, Zulkhairi Azizi Zainal; Jesse, Faez Firdaus Abdullah (Jurnal Medik Veteriner, 2025)
Bovine Viral Diarrhoea (BVD) is caused by pestivirus, which has an economic impact on the ruminant industry. Most study focuses on cattle as the most affected species having detrimental effects on the reproductive soundness. However, the role of small ruminants in BVD transmission requires further understanding as they can also be affected by BVD. Thus, a cross-sectional study was carried out in Selangor with an objective (1) to determine the seroprevalence of BVD in cattle, deer, sheep, and goats and (2) to identify the associated risk factors of BVD. A total of 596 healthy animals i.e., 176 cattle, 212 goats, 100 sheep and 108 deers were randomly selected and sampled between 2021 to 2024 in 19 selected farms in Selangor. Blood samples were collected from all of the animals and the serum samples were tested against the detection of antibodies against p80-125 protein (NSP2-3), a non-structural protein (NS3), highly conserved, and common to all strains of pestiviruses such as BVD, Border Disease (BD), and BVD-Antigen using a specific monoclonal antibody (Erns). The risk factors were analysed by running a univariate and multivariate logistic regression model compiled using a backward-selection procedure analysis to obtain the odds ratio (OR). This study found that the herds seroprevalence of BVD among the farms was 57.89% (n = 19). Cattle seroprevalence is 29.54% (n = 176), goats 11.3% (n = 212), sheep at 50% (n = 100), and deer at 0% (n = 108). Only one breeding ram was tested positive for the BVD-Antigen test. The key risk factors for BVD in cattle included being dairy cattle (OR = 12.60, p < 0.001), lactating (OR = 31.2, p < 0.001), raised in semi-intensive systems (OR = 106.08, p < 0.001), kept in cattle-only herds (OR = 26.32, p < 0.002), and being located in urban areas (OR = 191.95, p < 0.001). For small ruminants, significant risk factors included goats raised in intensive systems (OR = 6.73, p < 0.001) and female sheep (OR = 2.25, p = 0.047). The findings highlights that BVD seroprevalence in sheep and goats in Selangor, identifying a positive BVD antigen result in a breeding ram, emphasizing the sheep's role in BVD transmission. In short, the multi-species ruminant farming in Malaysia should be cautioned for the risk of BVD transmission.